Analysis of MSME Actors' Perceptions in Facing Digital Transformation (Case Study of MSME Actors in Situbondo Town Square) - Fais Makki; Moh. Fakhri Assiddiqi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Digital transformation has become an essential strategy for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) amid rapid technological advancements and changing consumer behavior. However, the level of acceptance and readiness among MSME owners to adopt digital technology varies, particularly for micro-scale businesses in regional areas. This study aims to analyze MSME owners' perceptions of digital transformation and identify the perceived benefits and challenges of implementing digital technology among MSMEs located around Alun-Alun Situbondo. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation involving purposively selected MSME owners. The findings indicate that most participants have a positive perception of digital transformation, recognizing its potential to expand market reach, increase sales, and improve communication with customers through social media and other digital platforms. Nevertheless, several obstacles remain, including limited digital literacy, inadequate technological skills, financial constraints, and insufficient mentoring. The synthesis of the findings suggests that the success of digital transformation depends not only on the readiness of MSME owners but also on support from local government, educational institutions, and other stakeholders through training programs, mentoring, and improved digital infrastructure. Therefore, policies focused on strengthening the digital capacity of MSME owners are needed to ensure sustainable digital transformation and enhance the competitiveness of MSMEs at both local and national levels.